Endothelial FOSL1 drives angiotensin II-induced myocardial injury via AT1R-upregulated MYH9 - Zhao Wen-jing; Qian Yi; Zhang Yi-feng; Yang Ai-hua; Cao Jia-xin; Qian Hong-yan; Liu Yi; Zhu Wei-zhong (Acta Pharmacologica Sinica, 2025)
Vascular remodeling represents a pathological basis for myocardial pathologies, including myocardial hypertrophy and myocardial infarction, which can ultimately lead to heart failure. The molecular mechanism of angiotensin II (Ang II)-induced vascular remodeling following myocardial infarction reperfusion is complex and not yet fully understood. In this study, we examined the effect of Ang II infusion on cardiac vascular remodeling in mice. Single-cell sequencing showed Ang II induced cytoskeletal pathway enrichment and that FOS like-1 (FOSL1) affected mouse cardiac endothelial dysfunction by pseudotime analysis. Myosin heavy chain 9 (MYH9) was predominantly expressed in primary cardiac endothelial cells. The Ang II type I receptor blocker telmisartan and the protein kinase C inhibitor staurosporine suppressed Ang II-induced upregulation of MYH9 and FOSL1 phosphorylation in human umbilical vein endothelial cells. Silencing MYH9 abolished Ang II-mediated inhibition of angiogenesis in human umbilical vein endothelial cells, and attenuated AngII-induced vascular hyperpermeability. We found that FOSL1 directly bound to the MYH9 promoter and thus activated transcription of MYH9 by the dual luciferase reporter and chromatin immunoprecipitation assays, leading to vascular dysfunction. In vivo, 6 weeks after injecting adeno-associated virus-ENT carrying the TEK tyrosine kinase (tie) promoter-driven short hairpin RNA for silencing FOSL1 (AAV-tie-shFOSL1), cardiac function represented by the ejection fraction and fractional shortening was improved, myocardial fibrosis was decreased, protein levels of phosphorylated FOSL1, MYH9, and collagen type I alpha were reduced, and cardiac vascular density was recovered in mice with endothelial Fosl1-specific knockdown in Ang II-infused mice. In ischemia-reperfusion mice, AAV-shFosl1 mice had a reduced infarct size and preserved cardiac function compared with control AAV mice. Our findings suggest a critical role of the FOSL1/MYH9 axis in hindering Ang II-induced vascular remodeling, and we identified FOSL1 as a potential therapeutic target in endothelial cell injuries induced by myocardial ischemia-reperfusion.